Political Economic Analysis of the Protection of Migrant Workers Victims of Human Trafficking Crimes - Ramadhan, Riki; Wicakaksana Prakasa, Satria Unggul (Universitas Negeri Semarang, 2024)
Human trafficking is a serious criminal threat that is organized and occurs globally, starting from within the country to abroad. The victims also vary, from adults to children under age. As happened to Adelina Sao, a migrant worker from Indonesia who was found dead in Malaysia on suspicion of abuse by her own employer. In previous research according to Brian Septiadi Daud, Indra Yohanes Kiling, Puanandini, and Simangunsong have studied that aspects related to the crime of human trafficking are highlighted through the role of the prosecutor's office in restorative justice as stipulated in Prosecutor's Office Regulation No. 15 of 2020, as well as identifying social factors, especially excessive lifestyle demands as the main cause of the crime of human trafficking. In addition, according to Puanandini, supervision and evaluation need to be emphasized in private companies and the government involved in sending migrant workers. Do not forget that the application of criminal sanctions for perpetrators of human trafficking is also enforced. However, until now there has been no study that specifically integrates a political economic perspective to analyze the protection of migrant workers who are victims of human trafficking. The urgency of this research is through a political economic perspective so that it can reveal the relationship between government policies, economic interests, and market forces that influence the protection of migrant workers. Thus, the political economic perspective has answered that the government must view migrant workers as subjects of development who require policies based on social justice.can encourage the creation of comprehensive protection of migrant workers' rights, including access to decent work, fair wages, and protection from exploitation.